SUCCESSIVE GAIN OF INSULATOR PROTEINS IN ARTHROPOD EVOLUTION. (4th June 2013) - Heger, Peter; George, Rebecca; Wiehe, Thomas
<x xml:space="preserve">Abstract</x> Alteration of regulatory DNA elements or their binding proteins may have drastic consequences for morphological evolution. Chromatin insulators are one example of such proteins and play a fundamental role in organizing gene expression. While a single insulator protein, CTCF (CCCTC‐binding factor), is known in vertebrates, Drosophila melanogaster utilizes six additional factors. We studied the evolution of these proteins and show here that—in contrast to the bilaterian‐wide distribution of CTCF—all other D. melanogaster insulators are restricted to arthropods. The full set is present exclusively in the genus Drosophila whereas only two insulators, Su(Hw) and CTCF, existed at the base of the arthropod clade and all additional factors have been acquired successively at later stages. Secondary loss of factors in some lineages further led to the presence of different insulator subsets in arthropods. Thus, the evolution of insulator proteins within arthropods is an ongoing and dynamic process that reshapes and supplements the ancient CTCF‐based system common to bilaterians. Expansion of insulator systems may therefore be a general strategy to increase an organism's gene regulatory repertoire and its potential for morphological plasticity.